Architectural Transformations in Network Services and Distributed Systems - Luntovskyy, Andriy; Spillner, Josef (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2017)
With the given work we decided to help not only the readers but ourselves, as the professionals who actively involved in the networking branch, with understanding the trends that have developed in recent two decades in distributed systems and networks. Important architecture transformations of distributed systems have been examined. The examples of new architectural solutions are discussed. Content Periodization of service development Energy efficiency Architectural transformations in Distributed Systems Clustering and Parallel Computing, performance models Cloud Computing, RAICs, Virtualization, SDN Smart Grid, Internet of Things, Fog Computing Mobile Communication from LTE to 5G, DIDO, SAT-based systems Data Security Guaranteeing Distributed Systems Target Groups Students in EE and IT of universities and (dual) technical high schools Graduated engineers as well as teaching staff About the Authors Andriy Luntovskyy provides classes on networks, mobile communication, software technology, distributed systems, data security as well as performs research on design of network infrastructures and services like clustering, clouds and IoT. He published two scientific books in Germany (2008, 2011) and twelve books in mother tongue in Ukraine. Josef Spillner performs research on service and cloud ecosystems and is the initiator of the Open Source Service Platform Research Initiative.